Traumatic Syringomyelias: A Critique on the Basis of the Vortex Effect Theory - Ziya Asan (Reviews in Clinical Medicine, 2022)
Introduction: The aim of the study was to evaluate the clinical and radiological follow-up of cases who had a history of spine trauma and were being followed up for a diagnosis of post-traumatic syringomyelia and to discuss the existing theories in the literature and the vortex effect in pathogenesis.Methods: Records of 44 patients who had a history of high-energy spinal trauma and diagnosed post-traumatic syringomyelia after their follow-up were retrospectively evaluated. Cases were evaluated under two groups based on the type of trauma those affected by axial forces and those affected by vertical forces. Results from spinal MRI scans of the cases were recorded. Pathogenesis was aimed to be revealed by uncovering the relationship of trauma type with syringomyelia localization and size.Results: The mean age was 39.8; 26 cases were male, and 18 were female. 10 (58.8%) cases presented cervical, 4 (23.5%) cervicothoracic, and 3 (17.6%) thoracic syringomyelias due to axial trauma. 6 (22.2%) cases presented cervical, 4 (14.8%) cases cervicothoracic, and 17 (62.9%) thoracic syringomyelias due to vertical forces. Segmental asymmetries were frequently encountered among their neurological findings.Conclusion: Syringomyelias appeared most frequently in the cervical and cervicothoracic junction due to the vertebral column being affected by axial forces, whereas in the case of vertical forces, it appeared most frequently in the thoracic segments. When considered along with the mechanisms of syringomyelia development, the appearance of syringomyelias can be explained by a vortex effect inside the central canal.